A prospective, observational, multi-center, post-marketing safety surveillance study of the GSK combined vaccine against diphtheria, tetanus, pertussis, poliomyelitis, and Haemophilus influenzae type b invasive infections (DTaP-IPV/Hib) in South Korean infants - Diego Mpia Elenge; Ju Sun Heo; Sung Shin Kim; Yun-Kyung Kim; Jang Hoon Lee; Stebin Xavier; Enas Bahar; Gaël Dos Santos; Adrienne Guignard (Human Vaccines & Immunotherapeutics)
In South Korea, a combined vaccine against diphtheria, tetanus, pertussis, poliomyelitis, and Haemophilus influenzae type b invasive infections (DTaP-IPV/Hib) is available since 2018 for vaccination of infants from the age of 2 months. This prospective, observational, non-comparative, post-marketing study evaluated the real-world safety of DTaP-IPV/Hib primary vaccination in eligible South Korean infants from the age of 2 months between 2018 and 2022. Infants were followed up for 30 days after each vaccine dose to assess the proportion of infants experiencing any adverse event (AE), including adverse drug reactions (ADRs), unexpected AEs, and serious AEs/serious ADRs (SAEs/SADRs). Of 660 infants vaccinated during the study period, 646 were included in the total safety cohort. A total of 194 AEs were reported in 143 (22.1%) infants; 158 AEs occurred after the first dose in 130 (20.1%) infants, 21 after the second dose in 20 (13.4%) infants, and 11 after the third dose in ten (8.1%) infants. The most frequent AEs by Medical Dictionary for Regulatory Activities Preferred Terms terminology were pyrexia (13.3%), injection site swelling (5.1%), and irritability (1.7%). Most of the AEs were mild, resolved without a medical visit, and were classified as possibly related to vaccination. The incidence proportions of ADRs, unexpected AEs, and SAEs/SADRs were 19.4%, 4.3%, and 0.9%, respectively. All SAEs/SADRs resolved after hospitalization or emergency room visit, and one event was possibly related to vaccination. These results are in line with the approved label and other national/international studies, confirming the acceptable safety profile of DTaP-IPV/Hib in the South Korean pediatric population.